Religion and local culture: Pillars of social harmony in post-conflict Aceh - Maimun; Suhendrayatna; Irwan Abdullah; Rusli Yusuf; Syamsulrizal; Sanusi; Irwan Putra; Gorkem Avci (Universitas Negeri Yogyakarta, 2025)
The prolonged conflict between the Free Aceh Movement (GAM) and the Government of the Republic of Indonesia has resulted in social disruption, collective trauma, and the weakening of community social structures. Although a peace agreement was reached through the 2005 Helsinki Memorandum of Understanding, the greatest post-conflict challenge lies in rebuilding trust, solidarity, and social harmony. An interesting phenomenon is the success of Acehnese society in achieving social stability through internal strengths, particularly a strong Islamic religious approach and deeply rooted local culture. This article aims to analyze the contribution of religious and local cultural approaches in fostering post-conflict social harmony in Aceh. This study is qualitative in nature, using a descriptive-interpretative approach. Data collection techniques included in-depth interviews, document analysis, and surveys. Key informants consisted of religious leaders (ulama), traditional leaders, former GAM combatants, women leaders, youth, and village officials located in former conflict-affected regions such as Pidie, North Aceh, and Bireuen. Data analysis employed a thematic approach through data reduction, categorization, interpretation of findings, and inductive conclusion drawing. The findings show that religious approaches, through the active roles of ulama, religious gatherings (majelis taklim), and Islamic boarding schools (pesantren), have been effective in restoring faith-based values and community social ethics. Meanwhile, local cultural elements such as peusijuek (traditional blessing rituals), gampong deliberations, and customary village institutions have served as effective means of social reconciliation, strengthening community ties and resolving horizontal conflicts. The synergy between religious values and local wisdom has formed a strong social system for maintaining peace and preventing future conflicts. In conclusion, religious and local cultural approaches have proven to be fundamental pillars in creating sustainable social harmony in post-conflict Aceh. This model can serve as a strategic reference for other conflict-affected regions seeking to build peace through local potential.